The inverse association between a fish consumption biomarker and gingival inflammation and periodontitis: A population‐based study. (27th February 2022) - Ottosson, Filip; Hultgren, Lina; Fernandez, Celine; Engström, Gunnar; Orho‐Melander, Marju; Kennbäck, Cecilia; Persson, Margaretha; Demmer, Ryan T.; Melander, Olle; Klinge, Björn; Nilsson, Peter M.; Jönsson, Daniel
Abstract: Aim: The metabolite 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropionic acid (CMPF) is a fatty fish–intake biomarker. We investigated the association between plasma levels of CMPF in relation to gingival inflammation and periodontitis case definition, as well as the extent and severity variables. Materials and Methods: The Malmö Offspring Study is a population‐based study, and the Malmö Offspring Dental Study (MODS) is its dental arm, including periodontal charting. Plasma CMPF was measured using liquid chromatography–mass spectrometry and studied in relation to periodontal diagnosis and parameters using multivariable linear or logistic regression modelling adjusting for age, sex, education, body mass index, fasting glucose, and smoking. Results: Metabolite data were available for 922 MODS participants. Higher CMPF levels were associated with less gingival inflammation ( β  = −2.12, p  = .002) and lower odds of severe periodontitis (odds ratio [OR] = 0.74, 95% confidence interval [CI]: 0.56 to 0.98). Higher CMPF levels were also associated with more teeth ( β  = 0.19, p  = .001), lower number of periodontal pockets (≥4 mm) ( β  = −1.07, p  = .007), and lower odds of having two or more periodontal pockets of ≥6 mm (OR = 0.80, 95% CI: 0.65 to 0.98) in fully adjusted models. Conclusions: CMPF, a validated biomarker of fatty fish consumption, is associated with less periodontal inflammation and periodontitis. Residual confounding cannot be ruled out, and future studies are warranted.